EFFECTS OF Pb ACETATE ADMINISTRATION ON Pb and Mg BONE LEVELS IN PIGEONS (COLUMBA LIVIA - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1995)
ABSTRACT: Thirty two pigeons, male with body weight of 200-380 grams were used as experimental animals, then divided into treated and control groups. The treated grotip (16 birds) were given 100 mglkg body weight orally twice a week for 12 weeks, and the control group (16 birds) were given disilled water Every three weeks, four birds in the control and treated groups were killed by evaporated chlorofrom, then a part of the radius ulna were taken for magnesium and lead analyses a using atomic absorption spectrophotometer (AAS). Data of magnesium and lead concentrations in bone were analyzed statistically with split plot design. The results of experiment indicated that the lead concentration in the treated bone, was higher (P